Collaborative learning through virtual tools: Analysis of the perception of student satisfaction of teaching performance - Omar Chamorro-Atalaya; Belmira Marcelo-Veliz; Guillermo Morales-Romero; Nicéforo Trinidad-Loli; Darío Villar-Valenzuela; Beatriz Caycho-Salas; César León-Velarde (Institute of Advanced Engineering and Science, 2022)
The objective of this article is to identify the results of the evaluation of collaborative learning through technological tools as part of the pedagogical strategies in the virtual teaching process. For the evaluation, the SERVQUAL model was used, through which it was identified that 97.73% satisfactorily evaluate the reliability and security of pedagogical strategies through technological tools used in collaborative learning in the teaching process in virtual environments. The optimal evaluation regarding the reliability of collaborative learning is 100% related to compliance with the syllable, to the teacher's disposition to help them in the use of technological tools and to the conformity of the technological tools used in the subject. Regarding the security of collaborative learning, 100% of the satisfactory evaluation is related to the trust and kindness that the teacher transmitted with the use of technological tools in teaching in virtual environments.